Mineração e conflito ambiental: atores sociais e interesses em jogo na extração de granito no município de Nova Venécia - ES - Borsoi, Adriana Maria (2007)
Governmental omission in regard to disorganized granite extraction has facilitated the operation of irregular mining in diverse regions of the country. As a example of this problem we show the reality of the municipality of Nova Venécia located in the north of the state of Espírito Santo where difficulties of the agricultural growth have contributes to the valuation of granite mining as an important economic alternative for local development. Using the concept of environmental conflict as a reference, the study describes governmental regulations and mediation of granite mining activities, identifying the actors and environmental processes involved in these activities, as well as examining the resulting conflicts by means of a case study of the municipality of Nova Venécia. Among the principle conclusions of this study, developed by documental research and field interviews the following points are highlighted: 1) In spite of the existence of a body of relatively well-structured legal procedures for governing organs responsible for regulating the activity, contradictions exist which permit licensing and functioning of mining enterprises without observing basic legal requirements; 2) the legislation demonstrated itself to be inefficient from a technical as well as from a democratic point of view regarding public participation to be able to respond to the contradictions and conditions involving the activity; 3) the social segments involved, government authorities, the local communities and mining workers, demonstrated themselves as politically fragile in the face of the economic interests therefore putting sustainable local development at risk; 4) the management of the granite sector by governmental authorities is focused on preoccupations with the physical environment, consequently with an environmental licensing procedure exclusively technical and bureaucratic with participation of organized society.